Spontaneous breaking of finite group symmetries at all temperatures - Pedro Liendo, Junchen Rong, Haoyu Zhang (SciPost Physics, 2023)
We study conformal field theories with finite group symmetries with spontaneous symmetry breaking (SSB) phases which persist at all temperatures. We work with two $λ φ^4$ theories coupled through their mass terms. The two $λ φ^4$ theories are chosen to preserve either the cubic symmetry group, or the tetrahedral symmetry group. A one-loop calculation in the $4-ε$ expansion shows that there exist infinitely many fixed points that can host an all temperature SSB phase. An analysis of the renormalization group (RG) stability matrix of these fixed points, reveals that their spectrum contains at least three relevant operators. In other words, these fixed points are tetracritical points.